Eco-Efficiency Products: A Guideline for Teak Utilization Over 13-15 Years - Theerathat Lertchamchongkul; Songwut Egwutvongsa (Academic Journal of Interdisciplinary Studies, 2022)
The objective of this research was to develop a guideline for teak utilization over 13-15 years. In this case, the population comprised one thousand, one hundred, and twenty-nine participants at the academic conference and Thai natural resource exhibition, while the group sampling included a visitor group comprising ninety-four people at the exhibition and young teak product sales at the level of deviation of 10 percent. In this case, a 5-point rating scale was used as a research tool employing structured questionnaires, with a reliability value at the level of 0.7842. The results found that the participants had satisfaction in the produced model from young teak at the excellent level, (Mean=4.202; S.D.=0.649) according to the eight fields of satisfaction assessment consisting of 1) Function, 2) Durability, 3) Economics, 4)Material, 5)Ease of Use, 6)Construction, 7)Aesthetics, and 8)Production. Therefore, there were the means of each satisfaction field at the same level with a significance of .05, and the research results in the community group could be applied to use with the utilization pattern of young teak for 13-15 years by increasing economic value for teak garden cultivation in various communities.

Received: 30 November 2021 / Accepted: 11 February 2022 / Published: 5 March 2022
Keywords: Agricultural and Environmental Management